Raba tal v Slovenskih goricah v obdobju 2000–2024 - Žiberna, Igor (Časopis za zgodovino in narodopisje, 2024)
This article deals with the changes in land use in Slovenske gorice over the period 2000–2024. It analyses the land use structures in both years and the changes in land use categories at the level of the Slovenske gorice as a whole and at the level of submicroregions. It also analyses the directions of land use change between the individual categories. Based on the ratio of newly created non-cultivated to newly created cultivated areas, we have also shown the coefficients of extensification at the level of sub-microregions and cadastral municipalities.
Keywords: arable land; ekstenzifikacija; extensification; land use; obdelovalne površine; raba tal; Slovenske gorice